Ethical and Legal Aspects in the Implementation of the Triage System in Extraordinary Events and Outbreaks after Covid-19 in Indonesia - Putro, Antonius Kuncup Wisnu Baroto Sutrisno; Suhartono, Slamet; Mangesti, Yovita Arie; Setyorini, Erny Herlin (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2025)
The Intensive Care Unit triage system is an option in disaster management efforts amidst limited human health resources. This study aims to analyze the ethical and legal aspects of implementing the triage system in a disease outbreak disaster. The method in this study is normative juridical. The study’s results indicate that although triage aims to save as many lives as possible, its practice often causes ethical problems, especially when choosing the most important patients. The technical guidelines for triage have been legally regulated, but legal protection for health workers is still limited, and the objective criteria for the triage process are unclear. This study found that strengthening ethical elements and legal protection in the triage system is very important so that its implementation does not cause injustice or violation of patient rights. Therefore, current regulations should be supplemented with more in-depth ethical guidelines and clear mechanisms for determining who is responsible for carrying out triage. The study recommends ethical training, regulatory alignment with bioethics standards, and integration of ethical reviews to enhance future triage system resilience.AbstrakSistem triase Intensive Care Unit menjadi pilihan dalam upaya penanggulangan bencana di tengah keterbatasan sumber daya manusia kesehatan. Tujuan penelitian ini untuk menganalisis aspek etis dan legal penerapan sistem triase pada kondisi bencana wabah penyakit. Metode dalam penelitian ini adalah yuridis normatif. Hasil penelitian menunjukkan bahwa meskipun triase bertujuan untuk menyelamatkan sebanyak mungkin nyawa, praktiknya sering kali menyebabkan masalah etis, terutama ketika memilih pasien mana yang paling penting. Pedoman teknis triase telah diatur secara hukum, tetapi pelindungan hukum tenaga kesehatan masih terbatas dan kriteria objektif proses triase belum jelas. Studi ini menemukan bahwa penguatan elemen etis dan pelindungan hukum dalam sistem triase sangat penting agar pelaksanaannya tidak menyebabkan ketidakadilan atau pelanggaran hak pasien. Oleh karena itu, peraturan saat ini harus dilengkapi dengan pedoman etis yang lebih mendalam dan mekanisme yang jelas untuk menentukan siapa yang bertanggung jawab atas pelaksanaan triase. Studi ini merekomendasikan pelatihan etika, penyelarasan peraturan dengan standar bioetika, dan integrasi tinjauan etika untuk meningkatkan ketahanan sistem triase di masa mendatang.